Cerium oxide nanoparticles and metformin increase the reliability of the prooxidant/anti oxidant balance and the survival of ageing rats - Nikitchenko, Yu.V.; Klochkov, V.K.; Kavok, N.S.; Karpenko, N.A.; Sedyh, O.O.; Nikitchenko, I.V.; Bozhkov, A.I.; Yefimova, S.L.; Seminozhenko, V.P. (Доповіді НАН України, 2020)
In comparison with the action of metformin — mimetic of the calorie restricted diet, which prolong the animals lifespan, it has been studied the effect of nanoparticles of cerium dioxide (CeO₂ NPs (1-2 nm)) on survival, physiological indices (the concentration of thyroxine, rectal temperature), as well as biochemical indices (content of lipid hydroperoxides, aconitase, glutathione peroxidase, glutaredoxin, glutathione reductase, NADP⁺ -dehydrogenase activities (glucose-6-phosphate-, malate- and isocitrate dehydrogenase)) in serum, liver mitochondrial and postmitochondrial fraction of ageing rats. It has been found that the prolonged use of CeO₂ NPs with drinking water (0.25-0.30 mg/kg of body weight per day) and metformin (100-110 mg/kg of body weight per day) from 670 days after the birth lead to a significant increase in survival (the median survival of control rats was 900, in animals treated with CeO₂ NPs — 960, and metformin — 990 days), a decrease in rectal temperature, a slowdown in the decrease in the level of thyroxine in blood, and normalization of the prooxidant/antioxidant balance in liver and blood tissues. Calculated integral index of reliability of prooxidant-antioxidant balance (reliability coefficient) in the studied tissues of rats in response to the application of the CeO₂ NPs increased 4.99 times, and metformin — 4.94 times compared to intact animals. The data obtained allow us concluding about the prospects of the CeO₂ NPs, as well as metformin for the development of geroprotector drugs, increasing the healthspan and survival of an ageing organism. У порівнянні з дією метформіну — міметика низькокалорійної дієти, що продовжує життя тварин, вивчається вплив наночастинок діоксиду церію (CeO₂ НЧ (1—2 нм)) на виживання, фізіологічні показники (концентрація тироксину, ректальна температура) та біохімічні показники (вміст ліпідних гідроперок сидів, активність ферментів аконітази, глутатіонпероксидази, глутаредоксину, глутатіонредуктази, НАДФ⁺-дегідрогеназ (глюкозо-6-фосфат дегідрогеназа, малат дегідрогеназа та ізоцитрат дегідрогеназа) у сироватці крові, мітохондріальної та постмітохондріальної фракцій печінки. Було встановлено, що тривале використання CeO₂ НЧ з питною водою (0,25—0,30 мг / кг маси тіла на добу) або метформіну (100—110 мг / кг маси тіла на добу) з 670 днів після народження призводило до значного збільшення виживання (медіана виживаності контрольних щурів становила 900 днів, у тварин, які отримували CeO₂ НЧ — 960 днів, і метформіну — 990 днів), зниження ректальної температури, уповільнення зниження тироксину в крові та нормалізації прооксидантно/антиоксидантного балансу в тканинах печінки та крові. Розрахований інтегральний показник надійності прооксидантно/антиоксидантного балансу (коефіцієнт надійності) у досліджуваних тканинах щурів у відповідь на використання CeO₂ НЧ зріс в 4,99 раза, а метформіну — у 4,94 раза порівняно з інтактними тваринами. Отримані дані дозволяють зробити висновки щодо перспектив наночастинок CeO₂, а також метформіну для розробки геропротекторних препаратів, що сприяють поліпшенню здоров’я та збільшують виживаність організму при старінні.